2019
DOI: 10.1177/0260106019888367
|View full text |Cite
|
Sign up to set email alerts
|

How does mindful eating without non-judgement, mindfulness and self-compassion relate to motivations to eat palatable foods in a student population?

Abstract: Background: Previous research acknowledges the impact mindfulness, mindful eating and self-compassion has upon weight regulation and motives to eat palatable foods, with mindful eating showing an increased impact of eating behaviours. Some research has identified that present moment awareness should be the primary focus of mindful eating. Aim: This research aimed to explore the relationship between mindfulness, self-compassion and mindful eating with motivations to eat palatable food. Methods: A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
1
25
2
3
Order By: Relevance
“…Furthermore, it was also shown that high self-compassion was linked to more mindful eating, lower disordered eating, and lower BMI (Mantzios et al, 2018a, b;Taylor, Daiss, & Krietsch, 2015). Recent studies have shown a clear link between self-compassion and mindful eating (Keyte, Egan & Mantzios, 2019;; however, this was not replicated in the current study as mindful eating was not signi cantly related to self-compassion in this population. Also, in the present study, a signi cant negative relationship was observed between self-compassion and BMI.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, it was also shown that high self-compassion was linked to more mindful eating, lower disordered eating, and lower BMI (Mantzios et al, 2018a, b;Taylor, Daiss, & Krietsch, 2015). Recent studies have shown a clear link between self-compassion and mindful eating (Keyte, Egan & Mantzios, 2019;; however, this was not replicated in the current study as mindful eating was not signi cantly related to self-compassion in this population. Also, in the present study, a signi cant negative relationship was observed between self-compassion and BMI.…”
Section: Discussioncontrasting
confidence: 58%
“…Recent research proposed that mindful eating assists in the gradual change of external to internal motivations when eating, such as hunger, when participating in mindful eating interventions (Mantzios, Egan & Asif, 2019), promoting heathier eating behaviours (Mantzios & Wilson 2014, 2015aMantzios & Giannou, 2014;Zeros et al, 2021), including an increased intake of fruit and vegetables (Dutt et al, 2018;Gilbert & Waltz, 2010), and reductions in high sugar and energy dense food consumption (Mantzios, Skillett & Egan, 2020;Mason et al, 2016). Research has also found a negative association between mindful eating and motivations to eat palatable foods (Keyte et al, 2019;, fat and sugar consumption (Mantzios, Egan, Hussein, Keyte & Bahia, 2018b), and grazing (Mantzios, Egan, Bahia, Keyte & Hussein, 2018c). Pierson, Goto, Giampaoli, Hart and Wylie (2019) found mindful eating to successfully reduce the intensity of food cravings and promoted control over dietary intake, when used as an intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between self-compassion and diet quality is less clear. Higher self-compassionate individuals have been found to display less motivation to eat palatable but unhealthy foods [23]. There is also evidence that daily fluctuations in self-compassion could play a role in the quality of the food eaten [24].…”
Section: Self-compassionmentioning
confidence: 99%
“…Similarly, mindful eating adopts such a definition of mindfulness but applies the definition to eating-and food-related experiences [18]. Mindful eating has been found to increase the pleasure in eating, while simultaneously supporting a reduction in fat and sugar consumption, grazing, impulsive food choice, compulsive eating and motivations to eat for any other reason apart from internal feelings of hunger and satiety [19][20][21][22][23][24][25][26][27][28][29][30]. The positive outcomes have also led to several programmes targeting mindful eating, such as the Mindfulness-Based Eating Awareness Training (MB-EAT) [31] and the Mindful Eating and Living (MEAL) [32], where people suffering from other chronic conditions such as type 2 diabetes [33], chronic kidney disease [34] and obesity [30,35] benefited in improving health behaviours and outcomes.…”
Section: Introductionmentioning
confidence: 99%